The Fiscal Contract up Close: Experimental Evidence from Mexico City - Anne Brockmeyer; Francisco Garfias; Juan Carlos Suárez Serrato (CESifo GmbH, 2024)
Can the provision of public goods strengthen the fiscal capacity of governments in developing countries and move them toward an equilibrium of widespread tax compliance? We present evidence of the impact of local public infrastructure on tax compliance, leveraging a large public investment experiment and individual property tax records from Mexico City. Despite the salience and large effects of these investments on access to infrastructure, property values, and local economic development, we find no changes in property tax compliance and can rule out even small increases. These null effects persist even when taxpayers are reminded about the tax-benefit link.
Keywords: H71; O23; H41; 330; tax compliance; public goods; infrastructure; development; Steuermoral; Grundsteuer; Gemeindefinanzen; Kommunale Investition; Öffentliche Güter; Kommunale Entwicklung; Mexiko-Stadt